The contribution of employer characteristics to continued employment of employees with residual work capacity: evidence from register data in The Netherlands - van Ooijen, Raun; Koning, Pierre WC; Boot, Cécile RL; Brouwer, Sandra (Scandinavian Journal of Work, Environment & Health, 2021)
' ' OBJECTIVES ': 'This study aimed to examine the contribution of employer characteristics to continued employment of employees with residual work capacity. Moreover, we examined whether the contribution of employer characteristics differs across types of employers and employees’ types of diseases. ' ' METHODS ': 'Register data on disability assessments and employment status of N=84 394 long-term sick-listed employees with residual work capacity were obtained from the Dutch Employee Insurance Agency between 2010 and 2017. The dependent variable was continued employment four months after the assessment. We linked employees to their (former) employer to measure sector, firm size, and workforce composition. The average employment outcome of all employees assessed in the same firm and year served as a proxy measure for the extent of implemented disability-related policies and practices. Using multilevel multiple regression analysis, we compared the relative contribution of employer characteristics with employees’ characteristics. ' ' RESULTS ': 'Employer characteristics accounted for 10% of the variability in employment outcomes. In comparison, employees’ socio-demographic and disease characteristics accounted for 13% of the variability. The prevalence of continued employment was lowest in smaller firms and construction and low-wage service-orientated sectors. Furthermore, there were sizeable differences in employment outcomes between similar employers in terms of size, sector and workforce-composition, particularly between larger firms and among employees with mental or musculoskeletal disorders compared to other diseases. ' ' CONCLUSIONS ': 'This study shows substantial differences between employers in facilitating continued employment of employees with residual work capacity. Encouraging firms to invest more in disability-related policies and practices may result in better employment opportunities for these employees.
Keywords: disability; disability-related policy; disability-related practice; employee characteristic; employer characteristic; employer characteristics; partial disability; register data; residual work capacity; The Netherlands; work capacity; work participation